Repetitive negative thinking as a transdiagnostic predictor of depression and anxiety symptoms in youth - McEvoy, Peter (SAGE Publications, 2017)
Repetitive negative thinking (RNT) is a transdiagnostic process associated with numerous emotional disorders. Most measures of RNT are disorder-specific, limiting utility in comorbid populations. Transdiagnostic measures of RNT have been developed in adults and are associated with anxiety and depression. However, a transdiagnostic measure is needed to assess RNT in adolescents as a potential vulnerability factor for emotional disorders. This study validates a transdiagnostic measure of RNT—Repetitive Thinking Questionnaire–10 (RTQ-10)—in adolescents (N = 840, Mage = 15.7 years). Exploratory and confirmatory factor analyses supported a unidimensional structure. The RTQ-10 manifested good internal consistency and measurement invariance across genders and age. RNT was equally associated with anxiety and depression symptoms irrespective of gender or age. Convergent validity was demonstrated by correlations with disorder-specific measures of RNT. These findings support the RTQ-10 as a reliable and valid transdiagnostic measure of RNT in adolescents.